2024
DOI: 10.1002/ejhf.3088
|View full text |Cite
|
Sign up to set email alerts
|

Deep phenotyping of p.(V142I)‐associated variant transthyretin amyloid cardiomyopathy: Distinct from wild‐type transthyretin amyloidosis?

Yousuf Razvi,
Adam Ioannou,
Rishi K. Patel
et al.

Abstract: AimsTransthyretin amyloid cardiomyopathy (ATTR‐CM) is an increasingly recognised cause of heart failure. 3‐4% of individuals of African descent carry a TTR gene mutation encoding the p.(V142I) variant, a powerful risk factor for development of variant ATTR‐CM; this equates to 1.6 million carriers in the USA. We undertook deep phenotyping of p.(V142I)‐ATTRv‐CM and comparison with wild‐type ATTR‐CM (ATTRwt‐CM).Methods & ResultsA retrospective study of 413 patients with p.(V142I)‐associated ATTR‐CM (ATTRv‐CM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Over recent years, it has become apparent that V122I-associated ATTRv-CM represents a particularly severe form of cardiac ATTR amyloidosis with poorer outcomes compared with other genotypic variants, including wild-type ATTR-CM. 19,[33][34][35] The present data need to be interpreted within the limitations of the study. This retrospective study was conducted in referral centers for the diagnosis and management of ATTR-CM.…”
Section: Discussionmentioning
confidence: 95%
“…Over recent years, it has become apparent that V122I-associated ATTRv-CM represents a particularly severe form of cardiac ATTR amyloidosis with poorer outcomes compared with other genotypic variants, including wild-type ATTR-CM. 19,[33][34][35] The present data need to be interpreted within the limitations of the study. This retrospective study was conducted in referral centers for the diagnosis and management of ATTR-CM.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, V142Iassociated ATTRv-CA presents with greater disease severity (including lower left ventricular EF) and faster disease progression compared with both ATTRwt-CA and non-V142I ATTRv-CA. 27,28 Recent data from a clinical trial in ATTR-CA supported the presence of reduced EF in a significant proportion of patients with a tendency to progress in ATTR-CA. 29 Therefore, among Black hospitalized patients with HFrEF, suspicion for ATTR-CA should be heightened and not restricted to patients with preserved EF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that homozygous patients with ATTRv cardiomyopathy were diagnosed at a younger age, suggesting an early disease onset and a more aggressive disease compared to heterozygous patients. 5 However, these results should be interpreted with caution due to the low number of homozygous patients, warranting the need for large cohort studies to validate this result.…”
mentioning
confidence: 89%
“…For example, in a cohort of patients with biopsy-proven ATTR cardiomyopathy, 9.6% of patients were homozygous for the p.V142I variant. 12 Similarly, Razvi et al 5 found a higher prevalence of homozygosity among patients with ATTR cardiomyopathy, representing 5.5% of the entire cohort. Moreover, it was found that homozygous patients with ATTRv cardiomyopathy were diagnosed at a younger age, suggesting an early disease onset and a more aggressive disease compared to heterozygous patients.…”
mentioning
confidence: 92%
See 1 more Smart Citation